Cloud as a Service Understanding the Service Innovation Ecosystem - Castro-Leon, Enrique; Harmon, Robert (Apress : Imprint: Apress, 2016)
This book uses principles of Service Science to explain the dynamics driving the adoption of cloud computing in the industry. Cloud as Service covers that evolution of enterprise computing platforms to application-specific cloud platforms or ASCPs aligned to business needs. This book also covers processes for developing and building ASCPs while also providing insight to executives, managers and technologists in corporations, large and small using or delivering cloud services, cloud service providers as well as equipment manufacturers and software and application vendors participating in cloud supply chains. .